Two-phase flow in metal monoliths: hydrodynamics and liquid-liquid extraction - Deshpande, Jaydeep B.; Gosavi, Abha; Kulkarni, Amol A. (Canadian Journal of Chemical Engineering, 2014)
This work aims to explore the application of metal monoliths as a scale-up option for efficient liquid-liquid extraction. The pressure drop, mass transfer and residence time distribution are measured for low Ca (approximate to 10(-5)) with monoliths having three different cell densities. The cross-over section between two monoliths was seen to enhance mixing in the column. However, the RTD of two-phase liquid-liquid up-flow was inferior to the single phase RTD. For higher cell density substrates, the cross-over zones seem to cause trapping of slugs due to non-superimposing channel ends. Relatively high shear rates through the film of continuous phase helped enhance the mass transfer rates, thereby helping to achieve the desired extraction in a short column. The entrance sections and cross-over zones between the monoliths adversely affected the extraction for higher cell density monoliths. The analysis of data supports use of low cell density monolith for better performance and scale up.
Keywords: capillary; hydrodynamics; liquid-liquid extraction; monolith; slug flow

Towards sustainable continuous production of azo dyes: possibilities and techno-economic analysis - Shukla, Chinmay A.; Kute, Mahesh S.; Kulkarni, Amol A. (Green Chemistry, 2021)
A novel continuous process for synthesizing azo dyes using a bubble column reactor is reported. Continuous experiments were successfully performed for Sudan-I dye and Solvent Yellow 16 dye with a yield [and productivity] of 92.04 +/- 3.50% [1.68 +/- 0.13 kg day(-1)] and 96.60 +/- 2.18% [1.92 +/- 0.04 kg day(-1)], respectively. Experiments were performed at a higher slurry concentration similar to 5% (w/w) without any clogging. The results were extended for performing a detailed techno-economic analysis for 5 TPD Sudan-I azo dye production as a case study. The results indicate that the cost of the continuous process is almost 4.68 times lower than that of the corresponding batch process. Furthermore, the footprint for a continuous plant can be lowered by 2.4 to 4.5 times when compared to the batch process depending on different refilling strategies for feed storage tanks. A continuous process may require 39-42% less water than the industrial batch process.

Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Bari, Atul H.; Shukla, Neerja; Gavriilidis, Asterios; Kulkarni, Amol A. (Biochemical Engineering Journal, 2023)
This work reports the transient behavior of continuous flow synthesis of gold nanoparticles (Au NPs) when subjected to perturbations in operating conditions using controlled experiments. The intricacies are captured through a detailed mathematical model. Reversed Turkevich protocol was used for synthesis of Au NPs. The synthesis was first studied in batch mode to investigate the reaction kinetics and reproducibility of the process. The optimal set of operating conditions viz., residence time, flow rate, temperature was then used for flow synthesis in a 2 m, 1/16 & DPRIME;Polytetrafluoroethylene (PTFE) reactor with micromixer. Reactor clogging was avoided by using segmented flow. Inline UV measurement was used for real time monitoring of the process. Transient experiments were performed by abruptly changing the operating conditions. A mathematical model was found to be accurate in predicting the transient behavior of the exit precursor concentration and the particle size for unsteady state synthesis. Even a small change in process variables for short duration was found to disturb the quality of Au NPs for a significantly longer duration. Of the three operating parameters, the effect of temperature variation was seen to have a prolonged effect where the system remained in unsteady state for long time.
Keywords: continuous flow synthesis; gold nanoparticles; Particle size; segmented flow; Unsteady behavior